84. Atypical presentation of Guillain-Barré syndrome in childhood: A clinical case. Issue 12 (December 2017) - Tronci, S.; Bianchi, F.; Butera, C.; Amadio, S.; Guerriero, R.; Natali Sora, M.G.; Comi, G.; Del Carro, U.
Abstract : A 31-months old child was admitted with a 4-day history of fever and weakness. The initial neurological examination revealed a meningeal syndrome with neck stiffness, without consciousness impairment. Head CT was normal. Analysis of CSF showed only increased level of proteins. Based on clinical manifestations, an empirical antibiotics and antiviral therapy was started. During the following 48 h, a progressive flaccid tetraparesis occurred. An ENG/EMG study was performed to exclude a peripheral involvement that showed decreased CMAP amplitude, partial motor conduction blocks/pseudo-blocks signs in the forearm segment of median and ulnar nerves and absence of F-waves. The MRI of spinal cord showed enhancement of the cauda equina. These data led to a diagnosis of polyradiculonevritis and a treatment with IVIG was performed with an initial stabilization of the neurological symptoms. At 24 days, patient's symptoms did not further recover and ENG/EMG was repeated showing: diffuse absence of CMAPs, reduction of SAPs, active denervation in all muscles. The final diagnosis was AMSAN, and another cycle of IVIG was administered. As signs of meningeal irritation may be consistent with meningitis or other diseases, it is important to recognize atypical features of pediatric GBS spectrum syndromes to achieve early diagnosis and treatment.